Implementation of MPPT Algorithm and Supervision of Shading on Photovoltaic Module - Latreche, S.; Badoud, A. E.; Khemliche, M. (Engineering, Technology & Applied Science Research, 2018)
This paper presents an implementation of MPPT (maximum power point tracking) algorithm based on real-time measurements and on model-based simulation. For the supervision of a photovoltaic module, different cases of shading are used. Attention was given on advanced control for the supervision of a photovoltaic system according to the need to maximize energy output. Experimental results verified the performance and the feasibility of the proposed system.